Transcript profiling during preimplantation mouse development - Zeng, Fanyi; Baldwin, Don A.; Schultz, Richard M. (Developmental biology, 2004)
Studies using low-resolution methods to assess gene expression during preimplantation mouse development indicate that changes in gene expression either precede or occur concomitantly with the major morphological transitions, that is, conversion of the oocyte to totipotent 2-cell blastomeres, compaction, and blastocyst formation. Using microarrays, we characterized global changes in gene expression and used Expression Analysis Systematic Explorer (EASE) to identify biological and molecular processes that accompany and likely underlie these transitions. The analysis confirmed previously described processes or events, but more important, EASE revealed new insights. Response to DNA damage and DNA repair genes are overrepresented in the oocyte compared to 1-cell through blastocyst stages and may reflect the oocyte's response to selective pressures to insure genomic integrity; fertilization results in changes in the transcript profile in the 1-cell embryo that are far greater than previously recognized; and genome activation during 2-cell stage may not be as global and promiscuous as previously proposed, but rather far more selective, with genes involved in transcription and RNA processing being preferentially expressed. These results validate this hypothesis-generating approach by identifying genes involved in critical biological processes that can be the subject of a more traditional hypothesis-driven approach.